Impact of Status quo and Resistance to Innovation on the Failure of Detection and Prevention Strategies of Drugs Control Committee in Malaysia - Zeng, Zhen (Frontiers in Psychology, 2022)
The detection and prevention strategies for drug control have gained significant attention by the drug control committees globally and need the researchers’ attention to improve these strategies worldwide. Hence, the current research investigates the impact of the status quo and resistance to the innovative nature of the drug control committee on the failure of detection and prevention strategies in Malaysia. The current article also analyses the mediating role of poor team performance among the status quo and resistance to the innovation nature of the drug control committee and the failure of detection and prevention strategies in Malaysia. The present study has employed the primary data collection ways such as questionnaires to gather the data from selected respondents. The researchers also applied the SPSS-AMOS to check the association among variables and testing of hypotheses. The results revealed that the status quo and resistance to the innovation nature of the drug control committee have a positive association with the failure of detection and prevention strategies in Malaysia. The findings also exposed that poor team performance significantly mediates between the status quo and resistance to the innovation nature of the drug control committee and the failure of detection and prevention strategies in Malaysia. This study guides the policymakers that they should develop the policies that eliminate the status quo nature and motivate the committee to adopt innovations that enhance the team performance and success of detection and prevention strategies in Malaysia.